Superstructure bridge selection based on Life-Cycle cost analysis for short and medium span bridges. (15th June 2023) - Leiva-Maldonado, Stefan L.; Bowman, Mark D.
Highlights: Decision makers are generally risk-averse and therefore, superstructure selection based on stochastic analysis is needed. The most cost-effective options implicitly consider the least amount of working actions during their service lives. Slab concrete bridges are preferable for span lengths shorter than 12 m for simply supported and continuous spans. Steel galvanized structures are preferable for span lengths between 12 m and 21 m for simply supported and continuous spans. Prestressed concrete bulb tees dominate the larger span lengths for simply supported and continuous span distributions. Abstract: Bridge life cycle cost analysis (BLCCA) is a method that evaluates the total cost of a structure. Historically, deterministic approaches of the method have been used for the cost-effective selection of maintenance/preventive alternatives for different projects. However, decision makers are inherently risk averse and deterministic approaches are not strong enough to do a comprehensive informed based selection. Therefore, implementation of stochastic methods could be beneficial for decision makers and structural engineers in the superstructure selection process. Based upon common practice in Indiana, three different span length ranges were selected and eight different superstructure types both in steel and concrete were evaluated. Substructures were neglected in the analysis. The analysis was conducted for span configurations that included simple spans, two and three span continuous girders, for each span range. Cost-effective life-cycle profiles for each superstructure type were used based on Indiana Department of Transportation experience. Both deterministic and stochastic analyses were performed. In general, the inclusion of long term-costs using BLCCA reduces the differences in cost-effectiveness between alternatives for the same span length. Galvanized steel options were found to be cost-effective for different span lengths, especially for shorter spans, while prestressed bulb tees were generally the best option for longer spans.